2016
DOI: 10.1038/ncomms13478
|View full text |Cite
|
Sign up to set email alerts
|

VCAM1 acts in parallel with CD69 and is required for the initiation of oligodendrocyte myelination

Abstract: Oligodendrocytes differentiate to wrap their plasma membranes around axons, forming the myelin sheath. A neuronal cue is one of the regulator elements controlling this process. Here, we demonstrate that VCAM1, which plays a key role throughout the immune system, is also expressed in oligodendrocytes, where it regulates the initiation of myelination. VCAM1 knockout mice exhibit reduced myelin thickness. Decreased myelin thickness is also observed in mutant mice of α4 integrin, which is a neuronal VCAM1 ligand. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 50 publications
3
31
0
Order By: Relevance
“…Several transcription factors are involved in the maturation of OPCs, such as Olig2, Nkx2.2, which promotes the maturation of OPCs [28,29]. Rcent research has suggested that VCAM1 knockout mice exhibit reduced myelin thickness, VCAM1 contributes to the initiation of myelination [30]. The present results showed that the ratio of NG2/Olig2positive OPCs remarkably decreased in the corpus callosum at 14 days after ischemia-hypoxia.…”
Section: Discussionsupporting
confidence: 52%
“…Several transcription factors are involved in the maturation of OPCs, such as Olig2, Nkx2.2, which promotes the maturation of OPCs [28,29]. Rcent research has suggested that VCAM1 knockout mice exhibit reduced myelin thickness, VCAM1 contributes to the initiation of myelination [30]. The present results showed that the ratio of NG2/Olig2positive OPCs remarkably decreased in the corpus callosum at 14 days after ischemia-hypoxia.…”
Section: Discussionsupporting
confidence: 52%
“…Microglia mediate inflammatory responses in the CNS, but are also known to directly affect neurons, and vice versa, in the developing human as well as rodent CNS 4 , 6 , 28 , 29 . Recently, it has been established that microglia can initiate synaptogenesis, but also eliminate synapses during development and in disease 5 , 8 , 29 . Here, we began to probe the applicability of cerebral organoids for studying the interplay between human microglia and neurons, and for studying microglia-mediated inflammatory responses in situ.…”
Section: Resultsmentioning
confidence: 99%
“…9f). Genes such as cathepsin L (Ctsl), semaphorin 5A (Sema5a), and synaptotagminlike 2 (Sytl2) are highly expressed by differentiating OLs 49 , whereas vascular cell-adhesion molecule (Vcam1), sodiumcalcium exchanger-solute carrier family 8 member A3 (Slc8a3), and disheveled-associated activator of morphogenesis 2 (Daam2) play a causal role in OL differentiation or myelination [50][51][52] .…”
Section: Resultsmentioning
confidence: 99%